2005
DOI: 10.1039/b507776a
|View full text |Cite
|
Sign up to set email alerts
|

Click-chemistry as an efficient synthetic tool for the preparation of novel conjugated polymers

Abstract: The Cu(I)-catalysed 1,3-dipolar "click" cycloaddition is utilised as an efficient reaction for the preparation of novel fluorene-based conjugated polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
148
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(155 citation statements)
references
References 24 publications
2
148
0
5
Order By: Relevance
“…ii) The click reaction between bisazides and bisalkynes has led to the formation of novel conjugated polymers that showed interesting luminescent properties and can potentially be used as thermally structurable organic semiconductors, [111,112] while the poly-cycloaddition of a AB 2 monomer resulted in hyperbranched polymers. [113] Recently, Qing and co-workers reported fluoropolymers formed by poly(cycloaddition) that showed good thermal stability and solubility in common organic solvents.…”
Section: Discussionmentioning
confidence: 99%
“…ii) The click reaction between bisazides and bisalkynes has led to the formation of novel conjugated polymers that showed interesting luminescent properties and can potentially be used as thermally structurable organic semiconductors, [111,112] while the poly-cycloaddition of a AB 2 monomer resulted in hyperbranched polymers. [113] Recently, Qing and co-workers reported fluoropolymers formed by poly(cycloaddition) that showed good thermal stability and solubility in common organic solvents.…”
Section: Discussionmentioning
confidence: 99%
“…PEs were synthesized via one-pot/two-step/three-component CuAAC click SGP under the established optimal parameters and conditions: the solvent, NMP; duration of Step 1, 3 h; catalyst concentration, 20 mol%; solution concentration, 0.6 mol/L; catalyst/ligand pair, CuI/TEA, and its mole ratio, 1 : 5; temperature of Step 1,20 ∘ C, and of Step 2, 0 ∘ C for 4-6 h (until the solution became too viscous to stir) and 20 ∘ C for 9-11 h (i.e., for total 15 h).…”
Section: Synthesis Of Various Click Pes Under the Established Optimalmentioning
confidence: 99%
“…There are rather limited publications on the application of CuAAC in SGP for constructing either AB or AA-BB type polymeric backbones: Díaz et al reported about the synthesis of new adhesive polymers with N-arylsulfonamide moieties in the backbones [19]; Van Steenis et al obtained novel conjugated aromatic polymers with molecular weights (MWs) of 60-396 kDa ( 푊 ) by click SGP indicating that this reaction is suitable for constructing long-chain macromolecules with proper material properties [20]; AA-BB type aromatic polyethers having M 푊 of 27.0-32.8 kDa obtained by click chemistry were also reported [21]; liquid crystalline aromatic polyesters (PEs) [22], aliphatic polyethers constituting triethylene glycol [23], multifunctional poly(ethylene glycol)s (PEGs) [24], poly(alkyl aryl ether)s [25], poly(glycoamidoamine)s [26], linear polytriazoles composed of various 1,4:3,6-dianhydrohexitols [27], polytriazoles [28][29][30], and poly(aroyltriazole)s [31] were synthesized via CuAAC SGP as well. Triazole polymers (mostly polyethers on the basis of commercial polyols) were also synthesized under neat conditions, by azide-alkyne cycloaddition SGP at r.t. during 144 h without using metal catalyst [32].…”
Section: Introductionmentioning
confidence: 99%
“…Polímeros conjugados têm sido largamente explorados pela potencial aplicação em dispositivos optoeletrônicos, 165 diodos, 166 lasers orgânicos, 167 transistores de película fina 168 e dispositivos ópticos não lineares. 169 Reek e colaboradores 118 sintetizaram alguns polímeros conjugados por meio da reação "click", por exemplo 51 e 52 (Figura 8). Devido às propriedades luminescentes apresentadas por estes polímeros, são candidatos a uso em materiais fosforescentes.…”
Section: Figura 8 Polímeros Conjugados Com Propriedades Luminescentesunclassified